The Role of Community Support in Building Competitive Advantage in Tourism Villages: A Study of Kutuh Tourism Village - I Wayan Chandra Adyatma (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the role of community support as a determinant of the competitive advantage of tourism villages, considering the influence of Government Role and Destination Image. A quantitative approach was employed using a survey method involving community members engaged in tourism activities in Kutuh Tourism Village. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of reliability and validity tests indicate that all research constructs meet measurement quality standards, with Cronbach’s Alpha values as follows: Government Role 0.84, Destination Image 0.87, Community Support 0.91, and Competitive Advantage 0.85; Composite Reliability: Government Role 0.89, Destination Image 0.91, Community Support 0.94, Competitive Advantage 0.90; and AVE: Government Role 0.61, Destination Image 0.65, Community Support 0.70, Competitive Advantage 0.62. Structural model analysis revealed that Government Role (β = 0.36, t = 4.28, p < 0.001) and Destination Image (β = 0.43, t = 5.12, p < 0.001) positively and significantly affect Community Support, which in turn strongly influences Competitive Advantage (β = 0.50, t = 6.21, p < 0.001). These findings confirm that the competitive advantage of tourism villages is not solely determined by destination factors, but strongly depends on the level of community participation and support. The study provides important practical implications for tourism village management by emphasizing the strengthening of government involvement, the development of a positive destination image, and strategies to increase community participation sustainably.